Sistem Pakar Diagnosa Penyakit Tanaman Padi Menggunakan Metode Forward Chaining - Dadi Rosadi; Azril Hamid (STMIK Mardira Indonesia, Bandung, 2014)
The rice plant is one of the most important crops for mankind especially the Asian region where the plant is becoming the staple food. In the implementation of planting, the rice crop failure often occurs due partly to various diseases. However, to determine the types of diseases that attack required an agricultural experts, while the rice crop in the prevention of disease are often hit by the time due to the limited knowledge of the farmers and the lack of an expert skilled in the field that can go directly to the farmers. It is therefore necessary to overcome problems farmers a system that has knowledge as an expert in that it has knowledge of the symptoms and diseases of rice plants one type of disease caused by the pathogen. At this research-based expert system designed visual Delphi7 programming language using a rule base (rule-based) using a forward chaining inference method that is intended to help farmers in diagnosing diseases of rice plants. Expected rice plant diagnosis expert system using a forward chaining method, it could be a tool for farmers in their paddy plant disease diagnosis. Keywords: expert system; diagnosis; forward chaining